Public knowledge and awareness of the effect of diabetes mellitus on oral health - Azizah Bin Mubayrik; Aseel Al Mutairi; Haifa Al Mutairi; Aljoharah Bin Osseil; Norah Al Shahwan; Hanan Al Sohaibani (Elsevier, 2019)
Background: Diabetes mellitus (DM) is a common chronic disease with an increasing prevalence, affecting general and oral health, with several oral manifestations. A bidirectional effect of diabetes and periodontal diseases has been reported by many researchers. Aim: This study aimed to evaluate public awareness and knowledge of the association between DM and oral health among public living in Saudi. Methods: A cross-sectional survey was done in Saudi Arabia to determine knowledge, attitudes, and awareness to assess public regarding knowledge of DM-related oral health. Questionnaire was designed and distributed in local Language to a convenient sample group through social media outlets. Results: One hundred-ninety completed questionnaires. Our study findings indicated a general awareness of the association between DM and oral health but demonstrated a lack of awareness concerning some oral diseases related with DM. 134 out 190 participants (70.5 per cent) of the respondents confirmed that DM had a negative effect on oral health, and 46.9 per cent considered periodontal disease to have a negative effect on glycemic control. There was a reasonable knowledge concerning DM-related oral manifestations. In contrast, one third of the respondents considered it possible to treat patients with DM and with a blood glucose below 3.9 mmol/Which indicated that they think a low blood glucose level has good prognosis and 43.7 per cent agreed that patients with DM should take antibiotics after tooth extraction, while 33.7 per cent of respondents agreed that antibiotics should be administered prior to tooth extraction. These are important considerations for early diagnosis and onset management of oral disease. Conclusion: These findings indicate the need for targeted and specific health information education. They also support a greater need for collaboration between physicians and dentists.